Case Report: Chanarin-Dorfman Syndrome: A Novel Homozygous Mutation in ABHD5 Gene in a Chinese Case and Genotype-Phenotype Correlation Analysis - Liang, Bo; Huang, He; Zhang, Jiaxiang; Chen, Gang; Kong, Xiangsheng; Zhu, Mengting; Wang, Peiguang; Tang, Lili (Frontiers in Genetics, 2022)
The Chanarin–Dorfman syndrome (CDS) is a rare, autosomal recessively inherited genetic disease, whch is associated with a decrease in the lipolysis activity in multiple tissue cells. The clinical phenotype involves multiple organs and systems, including liver, eyes, ears, skeletal muscle and central nervous system. Mutations in ABHD5/CGI58 gene have been confirmed to be associated with CDS. We performed whole exome sequencing on a Chinese CDS patient with skin ichthyosis features mimicking lamellar ichthyosis, ectropion, sensorineural hearing loss, and lipid storage in peripheral blood neutrophils. A novel homozygous missense mutation (p.L154R) in ABHD5 gene was detected in this patient. Genotype-phenotype analysis in reported CDS patients revealed no particular correlation. Our findings further enrich the reservoir of ABHD5 mutations in CDS.